Management of Islamic Education on Indonesian Language Learning for Foreign Speaker Program - Siti Isnaniah; Fauzan Mustofa (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2020)
This study aims to compare the management of Islamic education for the BIPA (Bahasa Indonesia Penutur Asing/Indonesian Language Learning for Foreign Speaker) program at PTKI institutions in Indonesia and Al-Azhar University in Egypt from the aspects of the curriculum, institutions, teachers, students, and evaluation. This research used descriptive analytic method with a qualitative approach. In-depth interviews, content analysis, and observation were applied to collect the data. Data were analysed using the interactive model of Miles & Huberman and comparative analysis. The result of the research showed that BIPA management conducted by PTKI institutions and Al-Azhar university, Egypt in terms of institution, curriculum, language teachers, language learners, evaluation have applied islamic perspective (Aqeeda and Sharia) and Islamic values which are compatible with the regulation set by Direktur Jenderal Pendidikan Islam (Directorate General for Islamic Education) Number 6244 Year 2019. Referring to this regulation, both BIPA program at PTKI institutions and Al-azhar university are considered ready and successful.